Antibiotic resistance. (October 2021) - Edwards, Frances; MacGowan, Alasdair; Macnaughton, Emily
Abstract: Antimicrobial resistance continues to increase while the pipeline for new antibiotic development is drying up; after only eight decades of antibiotic use, bacterial infections that once were easily treated are becoming untreatable. Antimicrobials have enabled the advancement of many areas of medical practice. The successful outcomes of many surgical procedures and immunosuppressive treatments depend on antibiotic prophylaxis and the ability to treat infective complications. Antibiotic resistance, therefore, poses a serious threat to much of healthcare as we know it. Areas of particular concern are multiresistant carbapenemase-producing Gram-negative organisms, gonorrhoea and multidrug-resistant tuberculosis. Antibiotic resistance correlates with antibiotic use, so improved antimicrobial stewardship, with better prevention and diagnosis of infection, can help to conserve the currently available antimicrobial agents. Significant global action and investment, from both public and private sector funding, is required if the development of new anti-infectives is to keep pace with increasing resistance.